The impact of child maltreatment on the risk of deliberate self-harm among adolescents: A population-wide cohort study using linked administrative records - Nan Hu; Catherine L. Taylor; Jianghong Li; Rebecca A. Glauert (Child Abuse & Neglect, 2017)
Adolescents exposed to maltreatment have an elevated risk of deliberate self-harm (DSH). The aim of this study was to investigate longitudinally the effects of the number, timing, and type of maltreatment allegations on adolescent risk of having a DSH-related hospital admission, using linked data in Western Australia. A total of 351,372 children born between 1986 and 2000 were followed from birth up to the year 2010. Cox regression models were utilized, while controlling for a range of psychosocial covariates. Compared to children without allegations of maltreatment, children with unsubstantiated allegations only (aHR=1.04, 95%CI: 1.00–1.08, p<.01) and children with a substantiated allegation (aHR=1.10, 95%CI: 1.06–1.15, p<.001) all had significantly increased risk of DSH in adolescence. Among children with a substantiated allegation of maltreatment, the greater the number of allegations, the longer the exposure to maltreatment, and the more types of maltreatment experienced by a child, the higher the child's risk of DSH. However, this dose–response pattern was not found among children with unsubstantiated allegations only. This study calls for the early identification of children who are vulnerable to maltreatment, the better identification of the duration and severity of maltreatment experiences, and the provision of continued care and support, to reduce the child's DSH risk in adolescence.
Keywords: 330; child maltreatment; adolescent deliberate self-harm; administrative data linkage; birth cohort